2020
DOI: 10.1055/s-0040-1716902
|View full text |Cite
|
Sign up to set email alerts
|

Is Brain MRI Needed in Diagnostic Evaluation of Mild Intellectual Disability?

Abstract: Aim The purpose of our study was to suggest an imaging strategy and guidelines for the selection of the children with mild intellectual disability (ID) for magnetic resonance imaging (MRI), to avoid unnecessary imaging. Methods The brain MRIs and patient reports of 471 children were reviewed for the imaging findings and ID severity. The correlation between the clinical and brain MRI findings was analyzed in the 305 children with mild ID. Results Thirty-eight (12.5%) of the children with mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
1
Order By: Relevance
“…The majority of children had normal MRI results (62.5%), but abnormalities such as brain atrophy and thinning of the posterior aspect of the cerebral cortex were noted, similar to European research by Soto et al, which found a significant presence of cerebral abnormalities in children with mental retardation [18] . Only 30.6% of the children had epilepsy, contrasting with Jussila et al's findings, which showed a lower incidence of significant MRI findings in children with mild ID [19] . The study suggests cautious consideration of routine MRI for children with mild ID due to the need for sedation and the limited etiological insight it provides without specific ~ 18 ~ neurological deficits [20] .…”
Section: Discussioncontrasting
confidence: 65%
“…The majority of children had normal MRI results (62.5%), but abnormalities such as brain atrophy and thinning of the posterior aspect of the cerebral cortex were noted, similar to European research by Soto et al, which found a significant presence of cerebral abnormalities in children with mental retardation [18] . Only 30.6% of the children had epilepsy, contrasting with Jussila et al's findings, which showed a lower incidence of significant MRI findings in children with mild ID [19] . The study suggests cautious consideration of routine MRI for children with mild ID due to the need for sedation and the limited etiological insight it provides without specific ~ 18 ~ neurological deficits [20] .…”
Section: Discussioncontrasting
confidence: 65%